An investigation of the formulation and nutritional composition of modern meat analogue products - Benjamin M. Bohrer (Food Science and Human Wellness)
Meat analogues, or plant-based products that simulate the properties of traditional meat products, have secured a position in the conversation of protein foods. Rapid growth of the meat analogue industry is occurring in the global food marketplace in both the retail and food service sectors. The purpose of this review was to investigate the ingredients used in the formulation of modern meat analogues, evaluate the nutrient specifications of modern meat analogue products, and then form a comparison with traditional meat products. Based on this investigation, it was determined – firstly, the ingredients used in the formulation of modern meat analogue products make these products fit under the classification of ultra-processed foods; and secondly, the nutrient specifications of popular meat analogue products can effectively simulate the nutrient specifications of the meat products they are attempting to simulate. Therefore, based on these findings, modern meat analogue products can offer roughly the same composition of nutrients as traditional meat products, albeit with many different ingredients and a high level of further processing. Keywords: Plant-based meat, Simulated meat, Meat alternatives, Processed foods, Protein foods